2014
DOI: 10.1371/journal.pone.0096827
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Capsular Polysaccharide Gene Clusters in Kpc-Producing Klebsiella pneumoniae Clinical Isolates of Sequence Type 258 Involved in the Italian Epidemic

Abstract: Strains of Klebsiella pneumoniae producing KPC-type beta-lactamases (KPC-Kp) are broadly disseminating worldwide and constitute a major healthcare threat given their extensively drug resistant phenotypes and ability to rapidly disseminate in healthcare settings. In this work we report on the characterization of two different capsular polysaccharide (CPS) gene clusters, named cps BO-4 and cps 207-2, from two KPC-Kp clinical strains from Italy belonging in sequence type (ST) 258, which is one of the most success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 40 publications
3
44
0
Order By: Relevance
“…In fact, G. mellonella moths lack an adaptive immune response, and the model can be used only to approximate mammals' innate immune response to bacterial infections. However, the difference in virulence among the clade 1 and clade 2 strains observed in this work is consistent with the different prevalences observed for the two clades, with an overall predominance of clade 2 strains in settings of high-level endemicity of KPC carbapenemase-producing K. pneumoniae strains of CC258 (22,29).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…In fact, G. mellonella moths lack an adaptive immune response, and the model can be used only to approximate mammals' innate immune response to bacterial infections. However, the difference in virulence among the clade 1 and clade 2 strains observed in this work is consistent with the different prevalences observed for the two clades, with an overall predominance of clade 2 strains in settings of high-level endemicity of KPC carbapenemase-producing K. pneumoniae strains of CC258 (22,29).…”
supporting
confidence: 87%
“…KK207-1 and KKBO-1 are two previously described strains and are representative of the two clades of ST258 (clades 1 and 2, respectively) (22). The mgrB insertional mutant of KKBO-1 (named mutKKBO-1) was previously described (18), while the mgrB mutant of KK207-1 (named mutKK207-1) was obtained with the same approach as for mutKKBO-1 and carried an ISKpn18 insertion disrupting the mgrB gene.…”
mentioning
confidence: 99%
“…The cps locus in these strains was most similar to that in the bla KPC-2 -producing Kp13 strain from Brazil (17,18) and clade 2 strains in reference 8, cps in reference 19, and to the cps locus in the KPNIH strains, with more than 99.99% nucleotide identity throughout the 50-kb region. The cps locus in ST258a strains (wzi-29) was nearly identical to the cps locus in the ST258 clade 1 (8), in VA360 (ANGI00000000), a bla KPC-2 ST258 strain from Ohio, in KpMDU1 (AMWO00000000), a bla KPC-2 strain from Australia, and to cps 207-2 (19). Common to these ST258a strains is a shared IS1 insertion within the cps region.…”
mentioning
confidence: 91%
“…The in-depth molecular epidemiologic examination of the genome region from different clades of ST258 that have independently acquired bla KPC revealed that capsule polysaccharide biosynthesis regions cps-1 and cps-2 are likely involved in the global success of these clades (56,98). This region of diversification could be advantageous for K. pneumoniae isolates to change polysaccharide as a mechanism to evade host defenses.…”
Section: The Success and Virulence Factors Of K Pneumoniae St258mentioning
confidence: 99%